Transplantation of neural precursors generated from spinal progenitor cells reduces inflammation in spinal cord injury via NF-κB pathway inhibition - Karova, Kristyna; Wainwright, John V; Machova-Urdzikova, Lucia; Pisal, Rishikaysh V; Schmidt, Meic; Jendelova, Pavla; Jhanwar-Uniyal, Meena (Journal of neuroinflammation, 2019)
BACKGROUND: Traumatic spinal cord injury (SCI) triggers a chain of events that is accompanied by an inflammatory reaction leading to necrotic cell death at the core of the injury site, which is restricted by astrogliosis and apoptotic cell death in the surrounding areas. Activation of nuclear factor-κB (NF-κB) signaling pathway has been shown to be associated with inflammatory response induced by SCI. Here, we elucidate the pattern of activation of NF-κB in the pathology of SCI in rats and investigate the effect of transplantation of spinal neural precursors (SPC-01) on its activity and related astrogliosis. METHODS: Using a rat compression model of SCI, we transplanted SPC-01 cells or injected saline into the lesion 7 days after SCI induction. Paraffin-embedded sections were used to assess p65 NF-κB nuclear translocation at days 1, 3, 7, 10, 14, and 28 and to determine levels of glial scaring, white and gray matter preservation, and cavity size at day 28 after SCI. Additionally, levels of p65 phosphorylated at Serine536 were determined 10, 14, and 28 days after SCI as well as levels of locally secreted TNF-α. RESULTS: We determined a bimodal activation pattern of canonical p65 NF-κB signaling pathway in the pathology of SCI with peaks at 3 and 28 days after injury induction. Transplantation of SCI-01 cells resulted in significant downregulation of TNF-α production at 10 and 14 days after SCI and in strong inhibition of p65 NF-κB activity at 28 days after SCI, mainly in the gray matter. Moreover, reduced formation of glial scar was found in SPC-01-transplanted rats along with enhanced gray matter preservation and reduced cavity size. CONCLUSIONS: The results of this study demonstrate strong immunomodulatory properties of SPC-01 cells based on inhibition of a major signaling pathway. Canonical NF-κB pathway activation underlines much of the immune response after SCI including cytokine, chemokine, and apoptosis-related factor production as well as immune cell activation and infiltration. Reduced inflammation may have led to observed tissue sparing. Additionally, such immune response modulation could have impacted astrocyte activation resulting in a reduced glial scar.
Keywords: Cell Line, Transformed; transformované buněčné linie; modely nemocí na zvířatech; Male; Rats, Wistar; Inflammation; Transcription Factor RelA; Stem cells transplantation; NF-κB; cytokiny; signální transdukce; Gliosis; mužské pohlaví; potkani Wistar; Spinal cord injury; Signal Transduction; transplantace kmenových buněk; zánět; TNF-α; krysa rodu Rattus; Time Factors; Stem Cells; p65; Animals; lidé; Spinal Cord Injuries; Stem Cell Transplantation; Humans; poranění míchy; gliový fibrilární kyselý protein; zvířata; Rats; časové faktory; Disease Models, Animal; Glial Fibrillary Acidic Protein; Cytokines; glióza; kmenové buňky; transkripční faktor RelA